(untitled) (Baghdad Science Journal, 2017)
The anatomical study of the epidermis leaflet for seven species and variety wild belonging to the genus Medicago L. species are: M. constricta Dur., M. coronata L., M. intertexta L., M. intertexta.var. ciliaris L., M. laciniata L., M. lupulina L., M. minima L. and M. sativa L. were studied, The search included epidermis characters and stomatal complexes addition to venation system in leaflets. It is revealed through the study, epidermis leaflet type Amphistomatic (the stomata spread on the upper and lower surface) as well as the presence of three types of stomatal complexes namely: Anisocytic (the guard cells surrounded by three unequal cell size), Anomocytic (not differential from subsidiary cells in epidermis) and Anomotetracytic (four cells surrounding the guard cell is irregular and varied). The results showed variations in dimensions and forms stomata and nature vertical walls and tangent to the upper and lower surfaces. The venation system distinguish by all the species studied as one of the type Simple craspedodromous in this system all secondary veins and branching ends at the margin of the blade leaflets, this found in all species. But there are clear differences in the Areoles shape and type of vienlets and at the ends, where these characters taxonomic and diagnostic value of the task in the species under study.